2001
DOI: 10.1007/s003810000353
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal synostosis: results of surgical treatment in 210 patients

Abstract: From 1977 to 1996, 210 patients suffering from scaphocephaly, have been operated on in our institutions. The surgical technique depended on the patients age. Single wide sagittal synostectomy was performed in 155 babies aged less than 3 months, obtaining good cosmetic results. Patients older than 3 months needed more complex and aggressive procedures to achieve similar results. The conclusions is that sagittal suturectomy is the proper treatment in younger patients under 3 months of age, and that a greater eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 12 publications
3
44
0
1
Order By: Relevance
“…The initial postoperative CI of 75 or the 2-to 4-year postoperative CI of 73 was a good result, as compared with others. 2,4,6,12,15,18,22,23,[29][30][31][32]36,39,40,46,51 The decrease in CI that we observed over time is comparable to the limited available data on long-term outcome. 2,16 Adding a widening bridge complies with Fearon and colleagues' suggestion to overcorrect width to compensate for later growth restriction in that direction.…”
Section: Discussionsupporting
confidence: 85%
“…The initial postoperative CI of 75 or the 2-to 4-year postoperative CI of 73 was a good result, as compared with others. 2,4,6,12,15,18,22,23,[29][30][31][32]36,39,40,46,51 The decrease in CI that we observed over time is comparable to the limited available data on long-term outcome. 2,16 Adding a widening bridge complies with Fearon and colleagues' suggestion to overcorrect width to compensate for later growth restriction in that direction.…”
Section: Discussionsupporting
confidence: 85%
“…Morphological outcome studies indicate that variants of open vertex strip craniectomy often result in a residual scaphocephalic deformity, with a cephalic index ranging from 70 to 74, frequently below the population norm. 2,5,19,29,31,47 Calvarial remodeling, by contrast, as a more extensive procedure allows a comprehensive correction of the deformity, which usually returns the cephalic index to the normal population mean. 15,26,40,44 We do not believe that raised ICP can simply be attributed to a poor morphological outcome in a minority of cases in an otherwise successful procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The Sshape skin incision allowed for sufficient operative fields. The plasticity of the infant cranial vault is an important factor in this surgical technique 2) . The authors previously suggested that infantile calvarial normalization using a non-fixed procedure is…”
Section: Resultsmentioning
confidence: 99%
“…Scaphocephaly, which is the most common type of craniosynostosis, accounts for approximately 40 to 60% of the isolated suture synostosis, and occurs in 1 in 5,000 children at birth 2,5,8,18,26,27) . Numerous techniques have been used to correct scaphocephaly in infants including bilateral strip craniectomy, wide-strip craniectomy, the π procedure, total vertex craniectomy, endoscopic craniectomy and cranial vault remodeling with parietal flap cranioplasties 3,4,6,7,10,11,[13][14][15]17,18,20,22,23,[25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%